PENYELESAIAN TINDAK PIDANA PENCURIAN DI LUAR PENGADILAN BERDASARKAN HUKUM ADAT DI DESA TANJUNG ALAI KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Randi Ramadhan; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The customary settlement is an alternative which with the accumulation of cases in the Court, this customary settlement effort can be made as a reference to cases of minor criminal acts such as happened in Tanjung Alai Village in accordance with the customary provisions in each region, so customary settlement is also important to anticipate the accumulation of cases in court. The legal consequences that occur when the settlement of criminal theft is done through customary law, while the legal consequences that can be applied to the case of criminal theft ie: Bearing the goods stolen around the market in the Village Tanjung Alai or in the crowd with head in the bald, Replacing for stolen items, and Paying the customary fine which is in the form of 1 (one) goat.Essentially, evil is an act that is perceived as a deviant act. Settlement of criminal cases, In addition to settling them before the court, in the community of Tanjung Alai, there are still cases of crimes that are solved through customary law. This study aims to determine the existence of customary law and sanctions against violators of criminal law and whether the type of effective inisancsi as the legal basis in solving this case